Rotating cylinder and magnetic field on solid particles diffusion inside a porous cavity filled with a nanofluid - Aly, Abdelraheem M.; Mohamed, Ehab Mahmoud; Öztop, Hakan Fehmi; Alsedais, Noura (Wiley, 2021)
This study deals with the roles of a magnetic field and circular rotation of a circular cylinder on the dissemination of solid phase within a nanofluid-filled square cavity. Two wavy layers of the non-Darcy porous media are situated on the vertical sides of a cavity. An incompressible smoothed particle hydrodynamics (ISPH) method was endorsed to carry out the blending process concerning solid phase into nanofluid and porous media layers. Initially, the solid phase is stationed in a circular cylinder containing two open gates. Implications of a buoyancy ratio (N = -2: 2), Hartmann number (Ha = 0: 100), rotational frequency (omega=1 : 10), Darcy parameter (Da=10(-2):10(-5)), Rayleigh number (Ra=10(3):10(6)), nanoparticles parameter (phi=0:0.06), and amplitude of wavy porous layers (Alpha=0.05:0.15) on the lineaments of heat/mass transport have been carried out. The results revealed that the diffusion of the solid phase is permanently moving toward upward except at opposing flow mode (N<0) toward downward. The lower Rayleigh number reduces the solid-phase diffusions. A reduction in a Darcy parameter lessens the nanofluid speed and solid-phase diffusions in the porous layers. A reduction in Da from 10(-3) to 10(-5) diminishes the maximum of streamlines vertical bar psi vertical bar(max) by 13.19% at N=-2, by 46.75% at N=0, and by 74.75% at N=2.
Keywords: Incompressible smoothed particle hydrodynamics; porous media; rotating cylinder; solid phase; magnetic field